The Effects of Urban Geometrical Properties on Land Surface Temperature; the Case of the Tehran Metropolitan Area - Pouria Ameri; ُShahram Pourdeihimi; Saeed Mashayekh Faridani (صفه)
In the recent decades, the geometric layouts and morphological elements of cities have increasingly been recognised as influencing the formation and intensification of the urban heat island phenomenon, with many researches conducted on finding the indicators representing these issues in various scales. Although the spatio-temporal effects of these indicators, as well as models for their interpretation and classification has been the subject of some recent studies worldwide, these studies are almost entirely missing for Iranian cases. The present paper studies and assesses the relationship between the land surface temperature and the morphological parameters of the built environment according to the concept of local climate zones, which is a standard framework for describing the form and function of cities in urban climate studies. The local microclimate zones of the Tehran metropolitan area have been studied and assessed based on the method proposed by the World Urban Database and Access Portal Tools. They are classified under seventeen groups in terms of their building geometries and land cover, with a resolution of 100 meters, using Landsat 8 satellite imagery data over the course of a year, integrated by geographic information systems and earth monitoring tools such as Google Earth, ArcGIS and SAGA GIS. The results of spatial and statistical analyses showed that over a year, the highest intensity of surface urban heat islands was related to areas without structures, as well as large-scale, low-rise industrial zones, with high-density, high-rise, and low-density low-rise classes having the least differences with the average land surface temperature. Also, the high-density, low-rise and mid-rise structures have had the lowest average temperature in the whole city during the year.